2002
DOI: 10.1007/s10350-004-6191-3
|View full text |Cite
|
Sign up to set email alerts
|

Anoperineal Tuberculosis

Abstract: Tuberculosis should be suspected in all recurrent fistulas. Histologic examination of the excised tissue and a lung x-ray should be performed to avoid delay in diagnosing an easily curable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 6 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…Treatment involves drainage of perianal sepsis and appropriate medical antituberculosis treatment [299,300] (level IV, grade GP).…”
Section: Tuberculosismentioning
confidence: 99%
“…Treatment involves drainage of perianal sepsis and appropriate medical antituberculosis treatment [299,300] (level IV, grade GP).…”
Section: Tuberculosismentioning
confidence: 99%
“…The microbiology of chronic and non-Crohn's anal fistulae in 25 consecutive anal fistulae was studied prospectively in a London hospital, and only one patient had Mycobacterium tuberculosis grown [4]. Sultan et al [5] reported a case series of seven patients managed in a Parisian proctology unit over a 17-year period for anorectal tuberculosis. In their series, a typical case of anorectal tuberculosis would be an immigrant aged [50 years with poor socio-economic background.…”
Section: Discussionmentioning
confidence: 99%
“…Sultan et al documented data of seven cases of anoperineal tuberculosis observed between 1982 and 1999. An association with pulmonary tuberculosis was found in each case, as well [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Differentiating the condition from Crohn's disease with anoperineal localization can be difficult if there is no caseation or direct evidence of acid fast bacilli [19]. Bacteriological analysis is done by identification of Koch's bacilli by direct examination (Ziehle-Neelsen stain) and culture [9]. The diagnosis is supported by the clinical response to an antitubercular therapy [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation